HARMONISASI STANDARAKUNTANSI INTERNASIONAL: ANALISIS KRITIS DARI PERSPEKTIF ISLAM - Anis Chariri (Jurnal Dinamika Ekonomi & Bisnis, 2006)
AbstractHarmonisation of intemational accounting standard has stimulated a debate conceming the rel evance of international accounting standards to the development of accounting in developing countries. It is claimed that such harmonisation is intended to increase comparability of financial reporting between companies from different countries. However, this paper argues that harmonisation is more concerned with hegemony of US accounting in the international arena. From the Islamic perspective, a number of international accounting standards seem to be in the contradiction with Islamic values. As accounting is practised in a certain environment, it is sug gested that accounting standards should be developed based on unique characteristics of environ ment in which financial reporting practice takes placeKeywords: harmonisasi,  standar akuntansi, anglo-saxon, dan Islam